Fatigue of Materials II Advances and Emergences in Understanding - Srivatsan, T.S.; Ashraf Imam, M.; Srinivasan, R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The papers in this collection cover a diverse range of topics on the topic of fatigue of materials. The editors have grouped the papers into five sections. Sections 1 and 2 contain papers that (i) review the current state of knowledge both related and relevant to the subject of fatigue behavior of materials, and (ii) present new, innovative, and emerging techniques for experimental evaluation of the fatigue behavior. Sections 3 and 4 focus on advanced materials that are used in performance-critical applications in the aerospace and automotive industries, such as the alloys of titanium, nickel, aluminum, and magnesium. Section 5 presents papers relating to other materials of engineering interest, such as iron and steel, polymer, rubber, and composites.
Keywords: Building materials; Metals; Mechanical engineering; Structural Materials; Metals and Alloys; Mechanical Engineering